2021
DOI: 10.1177/13694332211046345
|View full text |Cite
|
Sign up to set email alerts
|

Axial compressive behavior of circular concrete-filled double steel tubular short columns

Abstract: This article investigates the axial compressive performance of concrete-filled double steel tubular (CFDST) short columns composed of circular section loaded concentrically. An experimental program comprised of compression tests on short columns is carried out to examine their structural performance. Axial compression tests on conventional concrete-filled steel tubular (CFST) columns and double-skin concrete-filled steel tubular (DCFST) columns are also performed for comparison purposes. The test parameters in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
(69 reference statements)
0
14
0
Order By: Relevance
“…For the TPSBC under the loading form B, its axial compressive behavior is similar to that of the concrete-filled steel tubular columns (Ci et al, 2022;Han et al, 2008Han et al, , 2014Li et al, 2017;Zhao et al, 2019). Three types of confined concrete are considered due to the different strengths of the segment concrete and sandwich concrete, and different lateral confinements, as shown in Figure 12.…”
Section: Analytical Modelsmentioning
confidence: 99%
“…For the TPSBC under the loading form B, its axial compressive behavior is similar to that of the concrete-filled steel tubular columns (Ci et al, 2022;Han et al, 2008Han et al, , 2014Li et al, 2017;Zhao et al, 2019). Three types of confined concrete are considered due to the different strengths of the segment concrete and sandwich concrete, and different lateral confinements, as shown in Figure 12.…”
Section: Analytical Modelsmentioning
confidence: 99%
“…The steel tube confines the infilled concrete effectively and acts as formwork during the construction. The CFST columns offer better mechanical performance in terms of strength, ductility, seismic and fire performance compared to the traditional reinforced concrete columns (Ahmed and Liang, 2021; Ahmed et al, 2022; Ci et al, 2021a; Ci et al, 2021b). Existing studies showed that confinement was more uniform for the circular cross-section than the square or rectangular cross-sections of CFST columns; therefore, the strength and ductility of square or rectangular CFST columns are lower than their circular counterparts (Sakino et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…1, where D0 and Di are the diameter of the outer and inner tube, respectively and t0 and ti are the thickness of the outer and inner steel tube, respectively. The inner tube provides additional confinement to the core concrete, thus the strength and ductility of a circular CFDST column are higher than those of a conventional circular CFST column [5][6][7]. Moreover, in a CFDST column, the sandwiched concrete between two tubes and the core concrete within the inner tube can be designed to have different strengths to maintain a good ductility.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on circular CFDST columns have been primarily focused on investigating the performance of short columns, where the length-to-diameter ratio (L/D0) was limited to 4 to prevent the global buckling from occurring [5,6,8,9]. A circular CFDST slender column with an L/D0 ratio greater than 4 may fail due to global buckling, which reduces the ultimate strength of the column significantly.…”
Section: Introductionmentioning
confidence: 99%